Relative importance of the Hercynian and post-Jurassic tectonic phases in the Saharan platform: a palaeomagnetic study of Jurassic sills in the Reggane Basin (Algeria) - (:unkn) unknown (My University, 2006)
In the intracontinental domain of the northwestern Saharan platform, the deformation of the Palaeozoic sedimentary cover is mainly attributed to a far-field effect of the Hercynian orogeny having occurred at the African-Laurusian plate boundary in the Late Carboniferous to Early Permian times. However, geological observations from different parts of Africa and Arabia provide evidence that several minor but widespread tectonic events occurred later, particularly during the Cretaceous. Contrary to elsewhere in the northwestern part of Africa, in the Reggane Basin, outcropping doleritic sills of Early Jurassic age are intruded in folded Palaeozoic sediments of Devonian to Carboniferous ages deposited before the Hercynian orogeny. In this favourable situation, a palaeomagnetic study of the Liassic dolerite is able to provide information on the tectonic history of the surrounding area independently from geological observations. The present study aims to quantify the relative proportion of tilting related to, respectively, the Hercynian and a post-intrusion phase, using a fold test based on the small circle analysis. This method proved to be very efficient to unravel these tectonic events. It shows that, in the studied area, the folds were initiated during the Hercynian phase, but mainly amplified during the post-intrusion phase which turned out to be the dominant one. In the Reggane Basin, the age of this second event is not geologically well constrained between probably Late Jurassic and Early Cretaceous. It could be the far-field effect of either the Cimmerian phase (∼140 Ma) or more likely the Austrian tectonic phase (Late Barremian, ∼125 Ma). The Late Barremian tectonic episode corresponds to a major event: the break-up of Western Gondwana, which led to the separation of Africa from South America and to the incipient fragmentation of the African plate into three major blocks. The conclusion drawn from the palaeomagnetic study in the Reggane Basin is
Keywords: African Research